Some problems of the Kansas grape grower - Werner, Albert A. (My University, 1907)
Introduction: The grape promises to become one of the most important fruits of Kansas. It is without question, our most certain fruit crop. An entire failure is scarcely known. The high quality of some of the best varieties is not equaled by any fruit we are able to grow. Its hygienic and food value is shown to be great. The demand for it in the fresh and preserved condition is constant and an over supply does not surfeit the consumer. The great variety of ways in which this fruit may be preserved makes it available the entire year. The vine is adapted to our changeable climate better than any other fruit. It endures great extremes of heat and drought and is less likely to be injured by insect pests and fungus diseases than most other fruits.
Citation: Werner, Albert A. Some problems of the Kansas grape grower. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Grape Growing; Grape Growing in Kansas; Grape Industry; Factors Affecting Grape Growing; Techniques for Growing Grapes; Theses